Perkembangan Nilai Ekspor Migas Dan Non Migas - Novita Syahriani; Muhammad Faishal Yahya; Sri Dewi Anggraini; Tiara Fadhillah; Sari Wulandari (LPPM Universitas Labuhanbatu, 2024)
It can be said that before the 1980s, oil and gas was the prima donna of Indonesia’s exports, so that the role of Indonesian oil and gas in International trade was very important. However, the role of oil and gas exports continues to decline. The purpose of this research is to analyze and understand the performance of oil and gas and non-oil and gas exports. This research is a qualitative research with a descriptive approach. The data source of this research is secondary data. In Indonesia, oil and gas and non-oil and gas are goods exported with the aim of becoming engines of economic growth that greatly affect the Indonesian economy. In the last 5 years, the value of oil and gas and non-oil exports has fluctuated. In 2018 it was 180012.7, in 2019 oil and gas and non-oil and gas exports fell by 167683.0, then fell again by 163191.8 in 2020, in 2021 it rose to 231609.5, and in 2022 where the data is still up to September, namely 219328.8. the export value of oil and gas and non-oil gas experienced unavoidable fluctuations, so that oil and gas and non-ooil and gas exports became unstable.